Dopamine precursor depletion influences pain affect rather than pain sensation. - Laura Tiemann; Henrik Heitmann; Enrico Schulz; Jochen Baumkötter; Markus Ploner (PLoS ONE, 2014)
Pain is a multidimensional experience, which includes sensory, cognitive, and affective aspects. Converging lines of evidence indicate that dopaminergic neurotransmission plays an important role in human pain perception. However, the precise effects of dopamine on different aspects of pain perception remain to be elucidated. To address this question, we experimentally decreased dopaminergic neurotransmission in 22 healthy human subjects using Acute Phenylalanine and Tyrosine Depletion (APTD). During APTD and a control condition we applied brief painful laser stimuli to the hand, assessed different aspects of pain perception, and recorded electroencephalographic responses. APTD-induced decreases of cerebral dopaminergic activity did not influence sensory aspects of pain perception. In contrast, APTD yielded increases of pain unpleasantness. The increases of unpleasantness ratings positively correlated with effectiveness of APTD. Our finding of an influence of dopaminergic neurotransmission on affective but not sensory aspects of phasic pain suggests that analgesic effects of dopamine might be mediated by indirect effects on pain affect rather than by direct effects on ascending nociceptive signals. These findings contribute to our understanding of the complex relationship between dopamine and pain perception, which may play a role in various clinical pain states.